Pagamento direto pelo ressegurador na insolvência da seguradora - Martins, Raphael de Oliveira Pister (2024)
This dissertation examines the practice of direct payment by the reinsurer in cases of insurer insolvency and its legal and economic impacts in Brazil. The study provides a historical and legal overview of the insurance and reinsurance market in the country. It explores the concept of reinsurance and its importance for insurers' financial stability. It also discusses the insolvency of insurers, focusing on the legal challenges that arise in this scenario, with particular emphasis on the application of Supplementary Law No. 126/07, which allows the reinsurer to make direct payments to the original insured in cases of insurer insolvency. The dissertation analyzes the complexities of such payments, including the independent nature of insurance and reinsurance contracts. It evaluates the economic and developmental effects of this practice on policyholders and the insurance market as a whole. Furthermore, it provides a comparative analysis with foreign experiences, such as those of the United States, England, and France, demonstrating the global relevance of the issue and the need for a shared understanding across jurisdictions. In conclusion, the dissertation finds that while direct payment by the reinsurer may offer an efficient solution in cases of insolvency, it presents significant challenges in terms of public policy and principles of bankruptcy law. This research has practical implications for the insurance sector, highlighting the need for a balance between protecting creditors and ensuring the economic viability of the industry